Diagnostic study of diabatic heating and potential vorticity during a case of cyclogenesis - M K , AL-MUTAIRI; H ABDEL , BASSET (MAUSAM, 2020)
On 16-17 November, 2015, north and middle regions of Saudi Arabia were hit by a case of cyclogenesisassociated with heavy rainfall. This work presents a diagnostic study of this heavy rainfallcase based on the analysis of diabatic heating and potential vorticity. The synoptic analysis investigate that the important dynamical factors that causes this case are the northward extension of Red Sea Trough, anticyclone over the Arabian Peninsula, a travailing midlatitude upper trough, moisture transport pathways and strong upward motion arising from tropospheric instability. The calculation of diabatic heating by the thermodynamic equation illustrate that the contribution of vertical temperature advection and the adiabatic term are opposite to each other during the period of study. The largest contribution of the horizontal cold advection occurs during the first two days while the largest contribution of the horizontal warm advection occurs during the maximum development days. The dynamics of the studied case are also investigated in terms of isobaric Potential Vorticity. It is found that the location of the low-level Potential Vorticity anomaly and the Potential Vorticity generation estimates coincides with the heating region, which implies that condensation supports a large enough source to explain the existence of the low-level Potential Vorticity anomaly.